2014
DOI: 10.1080/17441692.2014.986158
|View full text |Cite
|
Sign up to set email alerts
|

Schizophrenia interventions in Vietnam: Primary results from a cost-effectiveness study

Abstract: Schizophrenia is a highly disabling mental health disorder that imposes a considerable economic burden on a health care system. This paper aimed to examine the cost and effectiveness of alternative pharmaceutical interventions and the effects of family intervention (FI) for schizophrenia from the government perspective in order to introduce the most cost-effective intervention applicable to Vietnam. A Markov model was developed to estimate costs and health outcome over patients' lifetimes when using typical an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 20 publications
2
15
0
Order By: Relevance
“…Our findings regarding interventions for patients at CHR-P and with acute psychosis and for first-line oral antipsychotic medication for individuals with FEP and with TRS are consistent with published literature. [12][13][14][15][16][17][18][19] For first-line oral antipsychotic medication for individuals with FEP, both the schizophrenia WDM and the model developed by the NICE schizophrenia Guideline Development Group 7 found that no antipsychotic medication can be considered clearly more cost-effective than the other options. However, the schizophrenia WDM found amisulpride to be the most cost-effective option, while the NICE model suggests amisulpride was the least cost-effective option.…”
Section: Comparing Results With Published Literaturementioning
confidence: 99%
“…Our findings regarding interventions for patients at CHR-P and with acute psychosis and for first-line oral antipsychotic medication for individuals with FEP and with TRS are consistent with published literature. [12][13][14][15][16][17][18][19] For first-line oral antipsychotic medication for individuals with FEP, both the schizophrenia WDM and the model developed by the NICE schizophrenia Guideline Development Group 7 found that no antipsychotic medication can be considered clearly more cost-effective than the other options. However, the schizophrenia WDM found amisulpride to be the most cost-effective option, while the NICE model suggests amisulpride was the least cost-effective option.…”
Section: Comparing Results With Published Literaturementioning
confidence: 99%
“…Other five head-to-head economic evaluations, conducted in USA, Greece and Norway, considered olanzapine to be dominant over risperidone (Rosenheck et al, 2006;Tunis et al, 2006;Geitona et al, 2008;Furiak et al, 2009;Kim & Aas 2011). Six studies, conducted in USA, Canada, Mexico, Sweden and Vietnam, found risperidone to be dominant over olanzapine (Bounthavong & Okamoto 2007;Cooper et al, 2008;Mould-Quevedo et al, 2009;McIntyre et al, 2010;Lindström et al, 2011;Anh et al, 2015). Other papers, from Slovenia, Canada, USA, Belgium, Brazil, Spain and Germany, reported data that favor olanzapine or risperidone in the ICER analysis, depending on the WTP in the place of study (Obradovic et al, 2007;Cooper et al, 2008;Edwards et al, 2008;Knapp et al, 2008;De Ridder & De Graeve 2009;Lindner et al, 2009;Ascher-Svanum et al, 2012;Garcia-Ruiz et al, 2012;O'Day et al, 2013;Zeidler et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Heres et al (2006) observed that in head-to-head comparisons of antipsychotics, 90% of the papers present results that favors the sponsor. But with respect to the comparison of olanzapine and risperidone, there are non-funded studies that show results favoring one drug or the other (Rosenheck et al, 2006;Bounthavong & Okamoto 2007;Obradovic et al, 2007;Lindner et al, 2009;Kim &Aas 2011;Anh et al, 2015). Prospective design studies had difficulty to demonstrate significant difference between risperidone and olanzapine in terms of costs and outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…31, 16.1%) [41][42][43][44][45], five studies assumed antipsychotic medications increase patients' mortality risk (5/31, 16.1%) [35,36,[46][47][48], and one study assumed antipsychotic medications can both increase and reduce patients' mortality risk (1/31, 3.2%) [49]. In the six studies which assumed that antipsychotic medications can reduce patients' mortality risk, they assumed that patients taking antipsychotic medications are less likely to commit suicide and thus have lower mortality.…”
Section: Plos Onementioning
confidence: 99%